Project management : methods and studies - Dean, Burton Victor (Amsterdam ; New York : Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1985)
The book was developed during world war II and was subsequently extended in the major military and aerospace projects that were undertaken at that time. The book is concerned with both managerial problems and quantitative methods as they affect project management.
Volume II.
Includes bibliographical references.
hza 20/07/2018
Loans
Keywords: Project management